MAKNA LIRIK LAGU BORN THIS WAY LADY GAGA DI KALANGAN REMAJA PEKANBARU ( ANALISIS SEMIOTIK ROLAND BARTHES ) - Fitri Irma Susanti; Noor Efni Salam (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
Lady Gaga known as eccentric singer and songwriter worldwide. Her career as amusician recorded raise every years. Her fans spread around the world especially in Indonesia.Most of Lady Gaga fans in Indonesia are teenagers. Instability of teenage personality makestheir ability to filtering west culture decrease. A different view of western culture brought byLady Gaga will be the long-term impacts for teens.The purpose of this study is to find out what exactly the meaning of the text contained inthe lyrics of Born This Way song by separating denotation, connotation and myth. This researchused qualitative methods descriptive which the data was obtained through interviews,documentation, and reference materials. As well as using semiotic analysis technique developedby Roland Barthes to know what the meaning of the Born This Way song lyrics that written andpopularized by Lady Gaga. This research presented the subject is a fan of Lady Gaga and somepeople who considered able to provide supporting information. Researchers using purposivesampling technique to determined the informants. While the research object is the text of thelyrics of the song Born This Way is obtained directly from the original CD.The results showed that the meaning of the Born This Way song written by Lady Gaga isabout freedom in many ways, a vindication of social deviation, and support for minoritiesthroughout the world. It can be seen from the mention of the various races in the Born This Waylyrics such as Black, White, Beige, and Chola Descent. This song serves as a support for theadolescent desire to be free and diminish the awareness of the social norms prevailing in thecommunity in accordance with the results of interviews with several informants. Eventually teenstarted to accept the deviation as a matter of course and can be tolerated. The deviation such asbehave of the Gay, Lesbian and Bisexual which rife in the community.Keyword: Born This Way, Semiotics, Roland Barthes